L-Arginine and Asymmetric Dimethylarginine Are Early Predictors for Survival in Septic Patients with Acute Liver Failure - Thorsten Brenner; Thomas H. Fleming; Claudia Rosenhagen; Ute Krauser; Markus Mieth; Thomas Bruckner; Eike Martin; Peter P. Nawroth; Markus A. Weigand; Angelika Bierhaus; Stefan Hofer (Hindawi Limited, 2012)
Dysfunctions of the L-arginine (L-arg)/nitric-oxide (NO) pathway are suspected to be important for the pathogenesis of multiple organ dysfunction syndrome (MODS) in septic shock. Therefore plasma concentrations of L-arg and asymmetric dimethylarginine (ADMA) were measured in 60 patients with septic shock, 30 surgical patients and 30 healthy volunteers using enzyme linked immunosorbent assay (ELISA) kits. Plasma samples from patients with septic shock were collected at sepsis onset, and 24 h, 4 d, 7 d, 14 d and 28 d later. Samples from surgical patients were collected prior to surgery, immediately after the end of the surgical procedure as well as 24 h later and from healthy volunteers once. In comparison to healthy volunteers and surgical patients, individuals with septic shock showed significantly increased levels of ADMA, as well as a decrease in the ratio of L-arg and ADMA at all timepoints. In septic patients with an acute liver failure (ALF), plasma levels of ADMA and L-arg were significantly increased in comparison to septic patients with an intact hepatic function. In summary it can be stated, that bioavailability of NO is reduced in septic shock. Moreover, measurements of ADMA and L-arg appear to be early predictors for survival in patients with sepsis-associated ALF.